(untitled) (TAJ: Journal of Teachers Association, 2023)
Background: Papillary thyroid carcinoma (PTC) is the most frequent histologic type of all thyroid malignancies followed by follicular thyroid carcinoma (FC). Follicular variant of papillary thyroid carcinoma (FVPTC) is the second most common variant of PTC. A diagnostic dilemma may arise, when histologically the distinctive nuclear features are either not well developed or present focally within an encapsulated thyroid lesion. A panel of immunomarkers has been tested to overcome the limitation of histopathology. P63 is commonly used immunomarkers among them. Objectives: The aim of the present study was to see the expression of P63 in PTC including FVPTC and FC in order to evaluate their possible roles in the differential diagnosis between these two mimics. Patients and methods: This cross-sectional descriptive study was conducted over 44 cases with histologically confirmed papillary and follicular thyroid carcinoma. Immunohistochemistry was done for P63. Results: Out of the 44 cases, 39 were histologically diagnosed as papillary thyroid carcinoma (27 were classical PTC & 12 were FVPTC) and the rest 5 were follicular thyroid carcinoma. In the present study, P63 showed 74.4% positivity with varying intensity and extent of staining in papillary thyroid carcinoma. Positive immunoreactivity of P63 was highly significant in distinguishing papillary from follicular thyroid carcinoma (P=0.003). Conclusion: This study suggested that the use of P63 may be helpful in the diagnosis of papillary and follicular thyroid carcinoma along with histopathological examination. TAJ 2023; 36: No-2: 121-128